TATA KELOLA PARIWISATA PANTAI KETAPANG DI DESA SUNGAI CINGAM KECAMATAN RUPAT KABUPATEN BENGKALIS TAHUN 2017 – 2018 - Idayu, Arwita; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research entitled " Tourism Govenance Ketapang Beach In The Villages Of Sungai Cingam In The Rupat District Of Bengkalis District In 2017-2018" This research was motivated by the existence of Minister of Home Affairs regulation number 10 of 2009 about tourism which explains that tourism is a variety of tourism activities and is supported by various facilities and services provided by the community, businessmen, government, and local government. As for the formulation of the problem in this study is “how is the tourism Govenance Ketapang Beach In The Villages Of Sungai Cingam In The Rupat District Of Bengkalis District In 2017-2018”.The method used in this study is a qualitative method that describes data descriptively. Data collection techniques used were interviews, observation and documentation. whereas, the source of the data used is the primary data obtained from the location of the study in the form of research informants and subsequently supported by secondary data in the form of data documents.The results of this study indicate that The results of this study indicate that tourism management in the Village of Sungai Cingam has not run optimally according to the principles of good tourism governance. This is because the achievement of each principle has not been fully fulfilled. These factors include the activeness and synergy of stakeholders not yet fully realized, partnerships only reach the level of the village government and the partnership has not been widely felt and has not been able to encourage local ownership, training programs that have not been implemented, public aspirations are still general, promotion is still minimal and stands individually, as well as guidelines for monitoring and evaluating tourist attractions are still simple without any special indicators to measure the impact of tourism activities carried out. Keywords: Tourism, Government, Private Sector, Society